A Bergia in South America: on the neglected, possibly already extinct B. arenarioides (Elatinaceae) - Hassemer, Gustavo (Phytotaxa, 2020)
The only species of Bergia known from South America, B. arenarioides, was originally described as Merimea arenarioides in 1829 and has been surprisingly neglected in the literature and databases since after the publication of the treatment of the Elatinaceae for Flora brasiliensis in 1872. The species is only known from two gatherings, both from northern Minas Gerais, Brazil, the most recent of which is from 1914. In this work I designate a lectotype for the species, investigate and clarify the location of its type locality and discuss its taxonomy and nomenclature. I present this information aiming at fostering the search and eventual rediscovery of the species.